Macroalgae Communities In The Waters Of Tateli Village, Mandolang, And Mokupa Village Waters, Tombariri, Minahasa District, North Sulawesi Province - Turangan, Septiara; Kepel, Rene Charles; Mandagi, Stephanus V.; Mantiri, Rose O. S. E.; Menajang, Febry S. I.; Kambey, Alex D. (Sam Ratulangi University, 2024)
On the coast of Beton Panjang and Tasik Ria, there are tidal flats with white sand substrates and some seagrass beds (seagrass) and macroalgae. Until now, there is still limited research on macroalgae in Beton Panjang and Tasik Ria. However, studies on macroalgae, especially aspects of their anatomical characteristics, have not been carried out. Therefore, it is necessary to study the anatomical characteristics and structure of the community. Sampling was carried out at the lowest ebb with the help of an application (to find out the lowest ebb time). They are laying transects at each location for macroalgae data collection as many as 3 transect lines 50 m long drawn perpendicularly from the coast towards the sea with the assumption that the community is evenly distributed. The distance between transects is 30 m with a squared distance of 5 m. Each square is used for data collection measuring 1 x 1 m². Analysis of the density index and relative density in Beton Panjang coastal waters yielded a density value of 0.06 ind.m2 – 0,43 ind./m2. The lowest density value is in the speciesLaurencia papillosa and the highest is in speciesPadina australis With a total density of individuals per species of 0.43 ind./m2. In the coastal waters of Tasik Ria, the highest density index is for species Neomeris annulled with a value of 0.63 ind./m2. The highest diversity index value is in the coastal waters of Tasik Ria with a value of H' = 2.33, while the highest dominance index is in the coastal waters of Beton Panjang with a dominance value of D = 0.16. The highest wealth and equity values ​​are in the coastal waters of Tasik Ria with a value of d = 2.27 and E = 0.94. Keywords: macroalgae, Beton Panjang, Tasik Ria, anatomical characteristics Abstrak Di pesisir Beton Panjang dan Tasik Ria terdapat rataan pasang surut dengan substrat pasir putih dan beberapa hamparan lamun (seagrass) serta makroalga. Sampai saat ini, masih terbatas penelitian tentang makroalga di Beton Panjang dan Tasik Ria. Namun, kajian mengenai makroalga khususnya aspek karakteristik anatomi belum dilakukan. Oleh sebab itu, perlu dilakukan kajian karakteristik anatomi dan juga struktur komunitasnya.Pengambilan sampel dilakukan pada saat surut terrendah dengan bantuan aplikasi Tides (untuk mengetahui waktu surut terrendah). Peletakan transek pada masing-masing lokasi untuk pengambilan data makroalga sebanyak 3 garis transek sepanjang 50 m yang ditarik tegak lurus dari pantai ke arah laut dengan asumsi bahwa penyebaran komunitas merata. Jarak antar transek yaitu 30 m dengan jarak kuadrat yaitu 5 m. Setiap kuadrat dipakai untuk pengambilan data berukuran 1 x 1 m². Analisi indeks kepadatan dan kepadatan relatif di perairan pesisir Beton Panjang di dapat nilai kepadatan 0,06 ind.m2 – 0,43 ind./m2. Nilai kepadatan terendah ada pada spesies Laurencia papillosa dan yang tertinggi ada pada spesies Padina australis Dengan jumlah kepadatan individu perjenis 0,43 ind./m2. Pada perairan pesisir Tasik Ria, indeks kepadatan tertinggi ada pada spesies Neomeris annulata dengan nilai 0,63 ind./m2 . Nilai indeks keanekaragaman tertinggi ada pada pada perairan pesisir Tasik Ria dengan nilai H’= 2,33, sedangkan untuk indeks dominasi tertinggi ada pada perairan pesisir Beton Panjang dengan nillai dominasi D=0,16. Untuk nilai kekayaan dan kemerataan tertinggi ada pada perairan pesisir Tasik Ria dengan nilai d= 2,27 dan E= 0,94. Katakunci: makroalga, Beton Panjang, Tasik Ria, karakteristik anatomi.